Benefits and risks of walking football for healthy ageing: a narrative review - Ali Ahmed; Philip J Hennis; Ruth M James; Ian Varley; Alfie G Price; John Hough (BMJ Open Sport & Exercise Medicine)
The global ageing population necessitates public health strategies to address age-related health decline. While physical activity is widely recognised as beneficial, exercise referral schemes often struggle to sustain participation. Walking football, an adapted version of traditional football designed for middle-aged and older adults, offers a unique alternative by harnessing intrinsic motivators such as enjoyment and social interaction to encourage long-term engagement. This narrative review examines walking football’s potential as a public health intervention, focusing on its safety and physical and mental health effects. The results reveal that walking football’s slower pace and reduced physical contact make it accessible and safe for individuals with various chronic conditions. However, limited evidence on injury rates and the lack of standardised injury surveillance highlight the need for consistent data collection to evaluate long-term safety. Emerging research indicates modest improvements in cardiovascular health and body composition, though findings are constrained by small, predominantly male samples, limiting generalisability. Qualitative studies highlight positive mental health impacts for individuals with mental health conditions, including enhanced social connections, self-confidence and purpose in life. Nonetheless, quantitative evidence on mental health outcomes remains sparse, emphasising the need for robust studies with validated pre-post intervention measures. Overall, walking football shows promise as a safe strategy to promote physical and mental health among diverse populations. Further research is crucial to better understand its benefits, limitations and safety profile, enabling its effective integration into exercise referral schemes and social prescribing initiatives aimed at increasing physical activity and well-being in middle-aged and older adults.